2007
DOI: 10.1002/dev.20202
|View full text |Cite
|
Sign up to set email alerts
|

Early weaning decreases play‐fighting behavior during the postweaning developmental period of wistar rats

Abstract: We examined the influence of early weaning on the development of play-fighting behaviors and anxiety status in Wistar rats. Pups were divided into two groups, those weaned at postnatal day (PD) 16 (early-weaned group) and those weaned at PD30 (normally weaned group), and were housed in pairs of the same sex. Playful interactions were measured for each pair once a week from 4 to 7 weeks of age. Thereafter, during early adulthood, all the rats were subjected to the elevated plus-maze test. The frequencies of pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 38 publications
(56 reference statements)
4
14
1
2
Order By: Relevance
“…Furthermore, offspring of both sexes weaned at earlier time points have been shown to exhibit increased general activity levels as juveniles and in adulthood Laviola and Dell'Omo, 1997;Laviola, 1995, 2001;Terranova et al, 1998]. In rats, similar increases in anxiety-like behavior and activity have been observed in early-weaned offspring [Kanari et al, 2005;Shimozuru et al, 2007] though males appear to be more affected than females [Ito et al, 2006;Kodama et al, 2008]. Though the magnitude of the effect is somewhat lessened, these differences have also been reported amongst rat pups weaned at day 21 PN compared to those weaned at day 30 PN [Ferdman et al, 2007;Joffe and Levine, 1973].…”
Section: Weaning Age Influence On Anxiety-like Exploratory and Sociasupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, offspring of both sexes weaned at earlier time points have been shown to exhibit increased general activity levels as juveniles and in adulthood Laviola and Dell'Omo, 1997;Laviola, 1995, 2001;Terranova et al, 1998]. In rats, similar increases in anxiety-like behavior and activity have been observed in early-weaned offspring [Kanari et al, 2005;Shimozuru et al, 2007] though males appear to be more affected than females [Ito et al, 2006;Kodama et al, 2008]. Though the magnitude of the effect is somewhat lessened, these differences have also been reported amongst rat pups weaned at day 21 PN compared to those weaned at day 30 PN [Ferdman et al, 2007;Joffe and Levine, 1973].…”
Section: Weaning Age Influence On Anxiety-like Exploratory and Sociasupporting
confidence: 52%
“…In adult rats, ani-mals weaned at day 30 PN compared to day 21 PN were found to spend more time in contact and in social investigation with a novel same-sex animal [Ferdman et al, 2007]. Conversely, rats weaned at day 14 PN have been shown to exhibit reduced frequencies of play fighting compared to animals weaned later [Janus, 1987;Shimozuru et al, 2007], though some evidence suggests that during the very early juvenile period, rat offspring weaned at earlier time points may show an increase in play behaviors [Brunelli et al, 1989;Smith, 1991]. As the decrease in social investigation that we observe in R21 weaned offspring is limited to the first minute of contact, these weaning age effects may relate to a decrease in social neophobia among animals who have undergone the process of weaning through extended mother-infant contact.…”
Section: Weaning Age Influence On Anxiety-like Exploratory and Sociamentioning
confidence: 97%
“…Such relations are not always apparent though. For example, early weaning increases fearfulness and aggression in adulthood, but decreases play fighting in juvenile animals (Kikusui, Isaka, & Mori, 2005;Kikusui, Takeuchi, & Mori, 2004;Nakamura, Kikusui, Takeuchi, & Mori, 2003;Shimozuru et al, 2007). Interestingly, Rhesus monkey males that are peer-group reared as opposed to being reared in social groups in the presence of their mothers display significantly increased play fighting in comparison to mother-reared males (Goy & Wallen, 1979;Wallen, 1996;Wallen, Bielert, & Slimp, 1977).…”
Section: Discussionmentioning
confidence: 87%
“…Early-weaned pups were housed in a same sex pair whereas normally weaned pups were able to interact with both opposite sex and same sex littermates. In a previous study, we found that early weaning decreases play-fighting behavior during the postweaning developmental period (Shimozuru et al, 2007). Thus, the reduction in interactions among pups may have contributed to alterations in behaviors and brain development in early-weaned rats.…”
Section: Figurementioning
confidence: 93%